2017
DOI: 10.18203/2320-6012.ijrms20174594
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of herpes zoster in a tertiary care hospital

Abstract: Background: Herpes Zoster, which presents as a localized, painful cutaneous eruption is a common clinical problem, caused by reactivation of latent Varicella Zoster Virus (VZV) and is usually self- limiting in healthy adults. In this era of HIV infection, HIV seropositive patients are at increased risk of severe or disseminated cutaneous or visceral involvement. Aim was to analyse the clinical pattern and epidemiological factors of Herpes Zoster and to know the HIV prevalence among patients with Herpes Zoster.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Different studies reported different sero positivity of HIV in chickenpox patients during their studies. Baghel N et al, reported 33.6 % HIV positivity whereas Laxmisha C et al, reported 35 % HIV positivity in chickenpox patients 4 . Again there is various evidence of persistent of VZV DNA in immune cells either with HIV sero positive or negative 5 .…”
Section: Introductionmentioning
confidence: 98%
“…Different studies reported different sero positivity of HIV in chickenpox patients during their studies. Baghel N et al, reported 33.6 % HIV positivity whereas Laxmisha C et al, reported 35 % HIV positivity in chickenpox patients 4 . Again there is various evidence of persistent of VZV DNA in immune cells either with HIV sero positive or negative 5 .…”
Section: Introductionmentioning
confidence: 98%
“…Naturally it occurs only in humans. 2 Wider use of varicella vaccination leads to reduced prevalence of varicella. 3 It results in reduced chances of periodic re-exposure to varicella.…”
Section: Introductionmentioning
confidence: 99%